(untitled) (Medico Legal Update, 2020)
Hepatitis B virus (HBV) infection is a serious and common infectious disease of the liver, affecting millions of people throughout the world. The incubation period for HBV is 45-180 days, most commonly 60-90 days. Hepatitis B reactivation is the reappearance or rise of hepatitis B virus (HBV) DNA in the serum of patients with past or chronic HBV infection. Reactivation can occur in a variety of clinical settings, usually in the context of an immunosuppressed state or immunosuppressive therapy. The aim of study is to find out the reasons that lead to reactivation of hepatitis B virus. The study conducted during the period from September 2019 to February 2020 the sample size were 135 individuals include 85 patients and 50 control with 56.47% female and 43.53% male) blood samples. A 42 (49.41%) from patients have reactivated HBV positive results as detected by ELISA assay . A five samples at a rate of 5.88% from these are HBV reactivation by PCR technique.